Optimizing Competitive Advantage through Innovation Culture Based on Individual Performance with Quality of Work Life as a Moderator - Adya Hermawati; Endang Fatmawati; Rizki Dwi Ariyanto; Teguh Setiawan Wibowo (Image : Jurnal Riset Manajemen, 2025)
In the ever-evolving landscape of the tourism industry, small and medium-sized enterprises (SMEs) have emerged as vital contributors to economic growth and sustainability. This literature review, conducted in the past, delved into the intricate dynamics surrounding competitive advantage within SMEs operating in the tourism sector. Specifically, it explored the pivotal roles of innovation culture, individual performance, and the moderating influence of quality of work life (QWL) in optimizing competitive advantage. In the pursuit of conducting a thorough literature review, our research methodology encompasses a multifaceted approach designed to ensure the acquisition of high-quality data sources and the rigorous evaluation of pertinent studies. The review identified gaps, including a need for more empirical research and an exploration of contextual variations. Furthermore, the review underscored the significance of individual performance in SMEs. It highlighted the intrinsic motivation, job satisfaction, and competencies that propel employees to excel, ultimately contributing to the organization's competitive positioning. Quality of work life as a moderator emerged as a critical factor in enhancing innovation culture and individual performance. A theoretical framework was developed to address these gaps, outlining the interplay between innovation culture, individual performance, QWL, and competitive advantage. This framework offers guidance for future empirical investigations and provides a roadmap for leveraging these critical elements to bolster the competitiveness and sustainability of SMEs in the tourism sector.